Effect of a lignin-based polyurethane on adhesion properties of asphalt binder during UV aging process. (30th June 2020) - Peng, Chao; Huang, Shifan; You, Zhanping; Xu, Fang; You, Lingyun; Ouyang, Hui; Li, Tianjun; Guo, Chong; Ma, Hongchao; Chen, Pengxu; Dai, Jing
Highlights: Lignin-based polyurethane improves adhesion strength of asphalt. Lignin-based polyurethane prevents asphalt stripping off from aggregate. UV affects adhesion of lignin-based polyurethane modified asphalt weakly. Anhydride group and lignin-based benzene ring are essential to improve adhesion. Abstract: Polyurethane is gradually used to chemically modify asphalt binder due to its outstanding compatibility with asphalt binder. One of the plant wastes (lignin) containing hydroxyl groups on its surface can replace one of the raw materials (polyether polyol) to prepare lignin-based polyurethane (LPU). To investigate the adhesion properties of lignin-based polyurethane modified asphalt binder (LPUA) during UV aging process, LPUA was prepared by high-temperature blending of lignin, toluene diisocyanate and matrix asphalt binder (MA). The adhesion properties of asphalt binders were evaluated by the pull-off experiment, ultrasonic washing experiment and contact angle test. The pull-off experiment shows that the tensile strength of LPUA increases by 27.3% in comparison with that of MA. UV aging process has a fragile effect on decreasing the tensile strength of LPUA. The ultrasonic washing experiment testifies that LPUA before and after UV aging process can be effectively retained on the aggregate surface even under the dynamic water environment. The contact angle test displays that LPUA can preserve its adhesion and stripping energies of asphalt binder during UV aging process. Fourier transform infrared spectrometer (FTIR) analysis exhibits that anhydride group and lignin-based benzene ring in LPUA are beneficial to improve the adhesion properties of asphalt binders before and after UV aging process. Based on the above results, it can be concluded that LPUA has satisfactory adhesion properties during UV aging process.